Proteome evolution under non-substitutable resource limitation - Manu Tamminen (Nature Portfolio, 2018)
Organisms could respond to essential resource limitation by increasing metabolic efficiency or resource acquisition ability. Here, the authors experimentally evolve green algae under different resource limitations and show convergent evolution of core metabolism rather than resource specialization.